2018
DOI: 10.5312/wjo.v9.i12.300
|View full text |Cite
|
Sign up to set email alerts
|

Metallosis following a clip breakage in a total knee arthroplasty implant: A case report

Abstract: BACKGROUNDMetallosis describes the build-up of metal debris in the soft tissues after a period of metal on metal articulation. This debris can be asymptomatic or lead to catastrophic implant failure, which can present acutely, as in this case, or over a period of time. This report highlights how a metal clip used to hold the polyethylene liner to the tibial base plate broke 5 years after implantation, dislodged from its original position and went on to cause post-operative knee metallosis.CASE SUMMARYWe presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Usually, the breakdown and loosening of components are inevitable because of progressive metal and polyethylene degradation [ 6 ]. However, deterioration of the opposite compartment and polyethylene tibial insert wear may occur early causing metal-on-metal articulation, aseptic loosening, and metallosis [ 9 ]. A major cause of loosening is attributed to the failure of the polyethylene locking mechanism which impairs the control of the interface micromotion and causes a dissociation of the polyethylene insert from the tibial base plate and an unintended articulation of metal components [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the breakdown and loosening of components are inevitable because of progressive metal and polyethylene degradation [ 6 ]. However, deterioration of the opposite compartment and polyethylene tibial insert wear may occur early causing metal-on-metal articulation, aseptic loosening, and metallosis [ 9 ]. A major cause of loosening is attributed to the failure of the polyethylene locking mechanism which impairs the control of the interface micromotion and causes a dissociation of the polyethylene insert from the tibial base plate and an unintended articulation of metal components [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some designs use a metal clip to hold the polyethylene liner to the tibial base plate to provide more stability. Nevertheless, it has been reported that the breakage of this component is a potential trigger for prosthesis loosening and post-operative knee metallosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eventual outcome of this condition is local tissue damage and changes in tissue characteristics as a result of direct toxic effects and biologic reactions to metallic nanoparticles [29,30]. Lately, cases were diagnosed patients after total knee replacement [31][32][33][34][35][36][37], knee joint load absorber [38], and total hip replacement [39][40][41][42][43][44]. Although, metallosis is a well-established complication of MoM implants, emerging data reveal that it also may be a problem in non-MoM implants such as either metal-on-polyethylene (MoP) or ceramic-on-polyethylene (CoP) implants, perhaps related to modular corrosion [45,46].…”
Section: Orthopedic Metallosismentioning
confidence: 99%
“…Metallosis can cause a wide variety of local and systemic symptoms, including pseudotumours and neurocognitive disorders [1,2]. Metallosis in TKA has been described in a few case reports with different causes, including clip breakage of the insert, insert wear, and failure of the metal-backed patellar components [3][4][5].…”
Section: Introductionmentioning
confidence: 99%